“Ready to fly with a lust for life” : Utopian Performatives in The Cultural Schoolbag - Tronstad , Ragnhild (Nordic Theatre Studies, 2023)
The Cultural Schoolbag (TCS) is a national programme designed to provide all school pupils in Norway access to professional art and culture. On average three times a year, in their school time, children and youth get to experience art and culture in various forms, spanning literature, film, music, visual arts, cultural heritage, theatre, and dance. To build and maintain Norway as a democracy is an explicit aim of the programme. Securing all children and youth equal access to professional art and culture regardless of geography, economy, religious or cultural background is but one aspect of its democratic scope. Also important is the belief that being exposed to art and culture is instrumental in educating future citizens who are able, ready, and willing to take active part in a democratic society. Reflecting this rather utopian vision of TCS, the county municipality of Vestfold used to launch their TSC programme under the motto: “Livslysten og flyvedyktig”, in English; “Ready to fly with a lust for life”. In what sense, however, do these utopian rationales influence the programme that is offered in the schools? How, exactly, may performance events and theatre experienced in TCS contribute to bringing up citizens that are “ready to fly with a lust for life”? Presenting an outline of current ideological, cultural political, and educational discourses surrounding TCS, this study addresses how, and to what extent, political and educational guidelines have an impact on its artistic programme. Offering two recent TCS productions as examples, I discuss how the utopian spaces provided by these theatre and performance events prepare the grounds for enactment and reflection that may take performative effect in influencing the lives and futures of the participating children and youth.